The Role of CD1d and MR1 Restricted T Cells in the Liver - Huang, Wenyong; He, Wenjing; Shi, Xiaomin; He, Xiaoshun; Dou, Lang; Gao, Yifang (Frontiers in Immunology, 2018)
The liver is one of the most important immunological organs that remains tolerogenic in homeostasis, yet promote rapid responses to pathogens in the presence of a systemic infection. The composition of leukocytes in the liver is highly distinct from that of the blood and other lymphoid organs. In particular, the enrichment of innate T cells, i.e. invariant NKT cells (iNKT cells) and Mucosal Associated Invariant T cells (MAIT cells). In recent years, studies have revealed insights into their biology and potential role in maintaining the immune-environment in the liver. As the primary liver-resident immune cells, they are emerging as significant players in the human immune system, associated with an increasing number of clinical diseases. As such, the innate T cells are promising targets for modifying host defense and inflammation of various liver diseases, including viral, autoimmune as well as tumour origin. In this review, we emphasise and discuss some of the recent discovery and advance in examining the biology of the innate T cells, their recruitment and diversity in the liver system and their role in various liver diseases. With postulation on their potential application in immunotherapy.